Chromosome counts and karyomorphology of some species of Artemisia (Asteraceae) from Turkey - Tabur, Selma; Civelek, Semsettin; Oney, Signem; Ergun, Sadiye Betul Yilmaz; Kursat, Murat; Turkoglu, Ismail (Tubitak Scientific & Technological Research Council Turkey, 2012)
Chromosome numbers and karyotypes of some species belonging to the genus Artemisia L. (Asteraceae) were investigated, and chromosome counts of 12 species, 1 of which was counted for the first time, are presented with a thorough compilation of previously published data. All of the species studied belong to the subgenus Artemisia Chromosome numbers of 6 taxa confirmed the previous data. Additionally, karyotypes of 8 species were reported. Karyotype analyses of 6 Artemisia species are reported here for the first time. The basic chromosome numbers in the species studied were x = 8 and x = 9, with ploidy levels ranging from 2x to 4x and 6x. B chromosomes were also present in Artemisia incana (L.) Druce as 2n = 2x = 16 + 2B.
Türkiye'den bazı Artemisia (Asteraceae) türlerinin kromozom sayıları ve karyomorfolojisi
Keywords: Artemisia; chromosome numbers; karyotype; dysploidy; cytotaxonomy